2010
DOI: 10.11144/javeriana.umed51-4.bpsa
|View full text |Cite
|
Sign up to set email alerts
|

Bajo polimorfismo en el sistema de antígenos de leucocitos humanos en población mestiza colombiana

Abstract: Objetivo. Este trabajo tiene como objetivo describir la frecuencia de alelos y de haplotipos de antígenos HLA de clases I y II en población mestiza colombiana.Metodología. Se estudiaron 197 individuos colombianos no emparentados y 157 individuos emparentados que conformaban 53 familias, provenientes de diferentes regiones del país, remitidos para estudios de HLA de clases I y II por el método PCR-SSP a los laboratorios de inmunología del Hospital Militar Central de Bogotá y al Instituto de Referencia Andino.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our statistical analyses showed that the extended haplotype hla-a*24-b*35-drb1*04 was the most frequent among donor and recipient (table 3) and that the haplotypes hla-a*24-b*35, hla-b*35-drb1*04 and hlaa*24-drb1*04 as well as the alleles hla-a*24, hla-b*35 and hla-drb1*04 were also highly frequent in the two groups (table 1 and 2). These results are in agreement with previous reports in Colombian (22)(23)(24) and other Latin American populations (10) where these alleles and haplotypes are the most frequently found.…”
Section: Discussionsupporting
confidence: 94%
“…Our statistical analyses showed that the extended haplotype hla-a*24-b*35-drb1*04 was the most frequent among donor and recipient (table 3) and that the haplotypes hla-a*24-b*35, hla-b*35-drb1*04 and hlaa*24-drb1*04 as well as the alleles hla-a*24, hla-b*35 and hla-drb1*04 were also highly frequent in the two groups (table 1 and 2). These results are in agreement with previous reports in Colombian (22)(23)(24) and other Latin American populations (10) where these alleles and haplotypes are the most frequently found.…”
Section: Discussionsupporting
confidence: 94%
“…Some 15-mer peptide sequences were selected by the following criteria: i) sequences with %Rank≥2 (strong binders) for at least two out of three prediction tools for more than one HLA-DR allele evaluated; ii) identical or similar sequences (synonym substitutions) between L. panamensis, L. braziliensis, and L. major species; and iii) sequences different from their human homolog when applicable. HLA-DR alleles taken in these predictions were based on studies of the most frequent alleles in the Colombian population (Trachtenberg et al, 1996;Correa et al, 2002;Reyes et al, 2007;Arias-Murillo et al, 2010;Ávila-Portillo et al, 2010;Yunis et al, 2013).…”
Section: In Silico Analysis For T Epitopesmentioning
confidence: 99%